Transcriptomic and metabolomic analysis of changes in grain weight potential induced by water stress in wheat - Yanmei Gao; Maoya Jing; Meng Zhang; Zhen Zhang; Yuqing Liu; Zhimin Wang; Yinghua Zhang (Journal of Integrative Agriculture, 2024)
The sink strength of developing ovaries in wheat determines the grain weight potential. The period from booting to the grain setting stage is critical for ovary growth and development and potential sink capacity determination. However, the underlying regulatory mechanism during this period by which the wheat plant balances and coordinates the floret number and ovary/grain weight under water stress has not been clarified. Therefore, we designed two irrigation treatments of W0 (no seasonal irrigation) and W1 (additional 75 mm of irrigation at the jointing stage) and analyzed the responses of the ovary/grain weight to water stress at the phenotypic, metabolomic, and transcriptomic levels. The results showed that the W0 irrigation treatment reduced the soil water content, plant height, and green area of the flag leaf, thus reducing grain number, especially for the inferior grains. However, it improved the grain weight of the superior and inferior grains as well as average grain weight at maturity, while the average ovary/grain weight and volume during –3 to 10 days after anthesis (DAA) also increased. Transcriptomic analysis indicated that the genes involved in both sucrose metabolism and phytohormone signal transduction were prominently accelerated by the W0 treatment, accompanied by greater enzymatic activities of soluble acid invertase (SAI) and sucrose synthase (Sus) and elevated abscisic acid (ABA) and indole-3-acetic acid (IAA) levels. Thus, the sucrose content decreased, while the glucose and fructose contents increased. In addition, several TaTPP genes (especially TaTPP-6) were down-regulated and the IAA biosynthesis genes TaTAR1 and TaTAR2 were up-regulated under the W0 treatment before anthesis, which further increased the IAA level. Collectively, water stress reduced the growth of vegetative organs and eliminated most of the inferior grains, but increased the ABA and IAA levels of the surviving ovaries/grains, promoting the enzymatic activity of Sus and degrading sucrose into glucose and fructose. As a result, the strong sucrose utilization ability, the enhanced enzymatic activity of SAI and the ABA- and IAA-mediated signaling jointly increased the weight and volume of the surviving ovaries/grains, and ultimately achieved the trade-off between ovary/grain weight and number in wheat under water stress.